Modifikace polymerních folií UV zářením a chemickým roubováním - Neubertová, Viktorie; Knapová, Tereza; Kormunda, Martin; Kolská, Zdeňka (Chemické listy, 2018)
This work deals with the surface properties of several polymer foils and their changes before and after UV irradiation and subsequent grafting with cysteamine. The surface wettability was determined by goniometry from static contact angle measurement. Surface chemistry, polarity and charge were studied by the electrokinetic analysis. Chemical composition of surface was characterized by X-ray photoelectron spectroscopy. All of the employed methods confirmed a successful surface activation by UV radiation and chemical modification by cysteamine grafting. These changes depend strongly on exposure time of UV radiation.
Keywords: ultrafialové záření; Polymers; povrchové vlastnosti; polymery; Ultraviolet Rays; Surface Properties